2020
DOI: 10.1186/s13034-020-00345-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of family communication and function, and satisfaction with body image, on psychological well-being of obese girls: the mediating role of self-esteem and depression

Abstract: Background Obesity has become a global problem in childhood and adolescence. The objective of the present study was to investigate the impact of family communication and function, and body image satisfaction, on psychological well-being by considering: the mediating role of self-esteem and depression. Methods In this cross sectional study, 173 obese and overweight female students were selected and evaluated based on body image satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 75 publications
0
23
0
3
Order By: Relevance
“…As for the direction of the association between them, the majority of extant studies supported the family-driven effect (family function influences adolescent depressive symptoms), in which researchers regard family function as an important predictor of adolescent depressive symptoms. For example, some scholars found that adolescents living in highly dysfunctional families were prone to have negative self-cognition, which was a key trigger to the emergence of depressive symptoms in adolescents (34,35). Similar results were found among teenagers in China (36,37).…”
Section: Introductionmentioning
confidence: 52%
“…As for the direction of the association between them, the majority of extant studies supported the family-driven effect (family function influences adolescent depressive symptoms), in which researchers regard family function as an important predictor of adolescent depressive symptoms. For example, some scholars found that adolescents living in highly dysfunctional families were prone to have negative self-cognition, which was a key trigger to the emergence of depressive symptoms in adolescents (34,35). Similar results were found among teenagers in China (36,37).…”
Section: Introductionmentioning
confidence: 52%
“…Good family functioning can promote adolescent self-esteem ( Shi et al, 2017 ), reducing depressive symptoms ( Lorenzo-Blanco et al, 2016 ). Self-esteem plays a mediating role in family functioning and mental health ( Man et al, 2017 ; KavehFarsani et al, 2020 ). Based on these aforementioned findings, then, we proposed our second hypothesis as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that children who have family support, good coping strategies, and emotional security are likely to have a positive body image and greater resilience thus decreasing depressive symptoms. 35, 36 Moreover, we observed that few of our obese participants with depressive symptoms had developed unhealthy eating habits. “Limited eating” was reported among a few female obese children, that is, they used to share the majority of their lunch with their school friends.…”
Section: Discussionmentioning
confidence: 97%